The Teacher’s difficulties In Teaching English Grammar and Pronounciation in Speaking Skills of Middle High School Students In Karanganyar - Aulia Zulfa Indi Putri; Sudjito (IAI Nasional Laa Roiba Bogor, 2024)
When the meaning of a language becomes increasingly important in this modern era, knowledge of English grammar and vocabulary alone is not enough to achieve correct and targeted communication. According to Sugiyono (2016), explained that the way of pronunciation in English holds a very important key in learning English which is recognized as a foreign language (EFL). This factor of course not only facilitates language understanding by native speakers or those who have proficiency in a foreign language, but can also improve students' communication skills in a foreign language. According to Widiyanti, M, J, A., Wulandari, R, S., & Indaryanti (2016), explains that grammar can create difficult aspects in speaking English. English grammar can be learned and taught to students, but in practice it proves difficult to pronounce. According to Alameddine, M. M ., & Mirza, H., (2016), there are some teachers who do not place much importance on grammatical skills in English when explaining English material. English teachers must also pay more attention to how they can create interaction in class with the target language taught in class, such as through group assignments and stage performance assignments. Apart from that, English teachers must also pay attention to whether the students' pronunciation is correct or not. If there is a situation where the teacher does not attach much importance to correct and appropriate grammar, then students can often make mistakes due to habits in their first language. According to (Widiyanti, M, J, A., Wulandari, R, S., & Indaryanti (2016),explained that some teachers still believe that English pronunciation is also difficult for them and this thinking has a negative impact on their teaching methods or ways. The problem is that deficiencies in English pronunciation and grammar are not considered important in the curriculum design in many schools in Indonesia.